2008
DOI: 10.1111/j.1526-100x.2007.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Properties Following 55 Years of Secondary Forest Succession at Fort Benning, Georgia, U.S.A.

Abstract: We present results on changes in soil properties following land use change over an approximately 55-year period at Fort Benning, Georgia, U.S.A. Soil cores were taken at 129 locations that were categorized as reforested (field/ bare ground in 1944 and forest in 1999), disturbed (field/ bare ground in 1944 and 1999), or reference forests (forest in 1944 and 1999). Soil disturbance included historic agriculture (pre-1944) and military training (post-1944). Density in mineral soils exhibited a historic land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 45 publications
7
26
0
1
Order By: Relevance
“…However, our sites were broadly dispersed over a landscape comprised of similar topographies, they possess some similar soil characteristics, including soil type (fine loamy ultisols), grain size composition and mineralogy (Pierce 1974), and our results are consistent with numerous studies documenting higher soil compaction on previously cultivated versus uncultivated land (Compton et al 1998;Lemenih et al 2005;Maloney et al 2008), suggesting that the observed differences are the result of previous land use.…”
Section: Plant Species Compositionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, our sites were broadly dispersed over a landscape comprised of similar topographies, they possess some similar soil characteristics, including soil type (fine loamy ultisols), grain size composition and mineralogy (Pierce 1974), and our results are consistent with numerous studies documenting higher soil compaction on previously cultivated versus uncultivated land (Compton et al 1998;Lemenih et al 2005;Maloney et al 2008), suggesting that the observed differences are the result of previous land use.…”
Section: Plant Species Compositionsupporting
confidence: 87%
“…Following a peak of agriculture in the early 1900s, increasing farm consolidation led to the widespread abandonment of small farmlands across much of eastern North America (Flinn and Vellend 2005), and these postagricultural lands are often marked by distinctively different conditions than lands that have never been cultivated (Foster et al 2003). Soils on historically cultivated sites, for example, are often more compacted, have greater bulk density, lower organic content, altered pH, and less microbial biomass than comparable non-cultivated sites (Burke et al 1995;Compton and Boone 2000;Falkengren-Grerup et al 2006;Maloney et al 2008). The relationship between previous cultivation and soil nutrient availability is more variable and highly dependent on the type of agricultural regime followed (McLauchlan 2006), as well as the post-agricultural plant community Kulmatiski et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that deforestation not only alters above-ground vegetation, but also leads to significant changes in the physical and chemical characteristics and biochemical cycles of soil ecosystems (Vitousek et al, 1989;Piccolo et al, 1994;Erickson et al, 2001;Maloney et al, 2007). The fate of nitrogen in deforested landscapes is relatively well known: lower total nitrogen pools (Piccolo et al, 1994;Rasiah et al, 2004), decreased nitrate levels (Piccolo et al, 1994;Reiners et al, 1994;Neill et al, 1997b;Rasiah et al, 2004), and an altered N-mineralisation and nitrification capacity Montagnini and Buschbacher, 1989;Steudler et al, 1991;Reiners et al, 1994) have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…Deforestation can significantly alter soil physical and chemical properties and biochemical cycles in rainforest landscapes, although different studies have reached varying conclusions about the extent to which reforestation re-establishes the full range of soil properties (Bashkin and Binkley, 1998;Rhoades et al, 2000;Rasiah et al, 2004;Silver et al, 2005;Zheng et al, 2005;Maloney et al, 2008;Paul et al, 2010). Nevertheless, there is a general consensus that reforestation can successfully restore many aspects of the nitrogen cycle, including nitrogen (N) stocks, nitrogen mineralisation, nitrate concentrations, and nitrification rates (Lamb, 1980;Robertson and Vitousek, 1981;Robertson, 1984;Vitousek et al, 1989;Rasiah et al, 2004;Scowcroft et al, 2004;Paul et al, 2010).…”
Section: Introductionmentioning
confidence: 98%